Optimalisasi Wireless Local Area Network Dengan Penerapan Hotspot Login Mikrotik Untuk Mengakses Aplikasi MyBest - Fahlepi Roma Doni Doni; Afit Muhammad Lukman; Budi Sudrajat (LPPM Universitas Bina Sarana Informatika Kampus Kabupaten Banyumas, 2025)
Abstract - As the development of the times in this century has had a significant impact on the progress of science in the field of technology, information technology has also developed, especially information technology has shown very rapid progress, infrastructure in the field of wireless computer networks that can support the creation of systems or Reliable applications are experiencing rapid development too. Technology in the field of Wireless Local Area Network (WLAN) networks is used so that we can use and utilize wireless networks well. A good wireless network is a stable connection when we use the network. For this reason, the author discusses the use of network technology, especially in the field of wireless networks by implementing bandwidth management, bandwidth capacity will be optimized using the QOS (Quality of Services) method and the author will also apply Hotspot login or hotspot user login to further optimize when clients or users visit. accessing the campus hotspot network, by implementing the QOS and Hotspot login methods, optimizing access to the hotspot network, it is hoped that there will be no more problems when users log in to the campus hotspot network. Keywords : WLAN, Hotspot login, QOS Abstrak - Seiring majunya berkembangan zaman pada abad ini memberikan dampak yang signifikan terhadap kemajuan ilmu pengetahuan dibidang teknologi, maka teknologi informasi ikut berkembang, khususnya teknologi dibindang informasi menunjukkan kemajuan yang sangat pesat, ifrastruktur dibidang jaringan komputer tanpa kabel (wireless) yang bisa mendukung untuk terciptanya sistem atau aplikasi yang handal ikut mengalami perkembangan pesat juga. Teknologi dibidang jaringan Wireless Local Area Network (WLAN) yang digunakan supaya kita bisa menggunakan serta memanfaatkan jaringan wireless dengan baik, jaringan wireless yang baik adalah stabilnya koneksi saat kita menggunakan jaringan tersebut. Untuk itu penulis membahas tentang pemanfaatan teknologi jaringan, terutama dalam bidang jaringan wireless dengan menerapkan manajemen bandwidth, kapasitas bandwidth akan dioptimalkan dengan metode QOS (Quality of services) dan penulis juga akan menerapan Hotspot login atau user login hotspot untuk lebih mengoptimalkan saat client atau pengguna akan mengakses jaringan hotspot kampus, dengan penerapan metode QOS dan Hotspot login pengoptimalan akses pada jarinagn hotspot diharapkan nantinya tidak ada kendala lagi saat user login pada jaringan hotspot kampus. Kata kunci : WLAN, Hotspot login, QOS